Presence and diversity of anammox bacteria in cold hydrocarbon-rich seeps and hydrothermal vent sediments of the Guaymas Basin - Russ, Lina; Kartal, Boran; Op Den Camp, Huub J.; Sollai, Martina; Le Bruchec, Julie; Caprais, Jean-Claude; Godfroy, Anne; Sinninghe Damsté, Jaap S.; Jetten, Mike S. (Frontiers in Microbiology, 2013)
Hydrothermally active sediments are highly productive, chemosynthetic areas which are characterized by the rapid turnover of particulate organic matter under extreme conditions in which ammonia is liberated. These systems might be suitable habitats for anaerobic ammonium oxidizing (anammox) bacteria but this has not been investigated in detail. Here we report the diversity and abundance of anammox bacteria in sediments that seep cold hydrocarbon-rich fluids and hydrothermal vent areas of the Guaymas Basin in the Cortés Sea using the unique functional anammox marker gene, hydrazine synthase (hzsA). All clones retrieved were closely associated to the ‘Candidatus Scalindua’ genus. Phylogenetic analysis revealed two distinct clusters of hzsA sequences (Ca. Scalindua hzsA cluster I and II). Comparison of individual sequences from both clusters showed that several of these sequences had a similarity as low as 76% on nucleotide level. Based on the analysis of this phylomarker, a very high interspecies diversity within the marine anammox group is apparent. Absolute numbers of anammox bacteria in the sediments samples were determined by amplification of a 257 bp fragment of the hszA gene in a qPCR assay. The results indicate that numbers of anammox bacteria are generally higher in cold hydrocarbon-rich sediments compared to the vent areas and the reference zone. Ladderanes, lipids unique to anammox bacteria were also detected in several of the sediment samples corroborating the hzsA analysis. Due to the high concentrations of reduced sulfur compounds and its potential impact on the cycling of nitrogen we aimed to get an indication about the key players in the oxidation of sulfide in the Guaymas Basin sediments using the alpha subunit of the adenosine-5’-phosphosulfate (APS) reductase (aprA). Amplification of the aprA gene revealed a high number of gammaproteobacterial aprA genes covering the two sulfur-oxidizing bacteria aprA lineages as well as sulfate-reducers.